Depressive episode and treatment outcomes in elderly individuals with tuberculosis: A prospective cohort study in Korea - Ahran Kim; Hyung Woo Kim; Ju Sang Kim; Jin Woo Kim; Yong Hyun Kim; Heayon Lee; Yeonhee Park; Jee Youn Oh; Hyeon-Kyoung Koo; Ock-Hwa Kim; Yun-Jeong Jeong; Yong-Soo Kwon; et al. (PLoS ONE, 2025)
Background Depression is common in the elderly and has been linked with poor tuberculosis treatment outcomes. Methods We conducted a prospective multicenter cohort study of adult aged ≥ 65 years with active tuberculosis in the Republic of Korea between 2020 and 2022. Sociodemographic and clinical data were obtained by interview. Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9), with a score ≥10 indicating a depressive episode. Logistic regression analyses were conducted to identify factors associated with depressive episodes and evaluate their association with treatment outcomes. Results Among the 361 elderly individuals with active tuberculosis who completed the questionnaire, 69 (19.1%) were classified as having a depressive episode. Depressive episodes were significantly associated with unemployment, higher comorbidity burden, and the presence of tuberculosis-related symptoms such as cough and constitutional symptoms. Functional impairment was reported in 39.6% (143/361) of all participants and increased with the greater severity of depressive symptoms. Suicidal ideation was observed in 19.7% (71/361) of all participants and was independently associated with alarming tuberculosis symptoms. Among the participants with rifampin-susceptible tuberculosis, those with depressive episodes had significantly lower treatment success rates (64.7% vs. 79.1%, p = 0.012). In multivariable logistic regression analysis, depression remained independently associated with reduced odds of treatment outcomes (adjusted odds ratio, 0.478; 95% confidence interval, 0.261–0.878). Conclusions In elderly individuals with tuberculosis, depressive episodes are associated with functional impairment, suicidal ideation, and poor treatment outcomes. Routine mental health assessments at tuberculosis diagnosis may help improve clinical outcomes in aging populations.